2015
DOI: 10.1007/s13277-015-3319-0
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1, a new biomarker of glioma progression, is associated with prognosis of patients

Abstract: Stanniocalcin-1 (STC1) is a secreted glycoprotein hormone and highly expressed in various types of human malignancies. Although evidence points to the role of STC1 in human cancers, the clinical significance of STC1 expression in glioma has not been established. Here, we investigated the relationship between STC1 expression and clinicopathological significance in glioma. In our study, we selected 60 cases of different grades glioma tissues to detect the expression of STC1. Data showed that the mRNA and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
3
32
1
1
Order By: Relevance
“…Some studies have suggested the anti-apoptosis effect of STC1, such as colorectal cancer [27, 28], breast cancer [19, 29], glioma tumor [11, 30], thyroid cancer [20, 31], ovarian cancer [32, 33] and so on. Others indicated the pro-apoptosis effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested the anti-apoptosis effect of STC1, such as colorectal cancer [27, 28], breast cancer [19, 29], glioma tumor [11, 30], thyroid cancer [20, 31], ovarian cancer [32, 33] and so on. Others indicated the pro-apoptosis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that STC1 is expressed abundantly in a variety of mammalian tissues including kidney [7], heart [8], lung [9], ovary [10], brain [11], muscular and skeletal tissues [12]. STC1 is highly conserved during evolution, and is implicated in several physiologies and pathologies, such as pregnancy [13], angiogenesis [14], inflammation and apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…ABCA13 was found to be upregulated in colorectal cancer (Hlavata et al ., 2012), and its high expression was related to less overall survival in metastatic ovarian serous carcinoma (Nymoen et al ., 2015). Another target of miR‐4484, STC1, also exhibited relatively higher expression in high‐grade gliomas as compared to low‐grade samples (Su et al ., 2015). Furthermore, samples with high expression of STC1 had worse overall survival as against samples with low STC1 expression (Su et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another target of miR‐4484, STC1, also exhibited relatively higher expression in high‐grade gliomas as compared to low‐grade samples (Su et al ., 2015). Furthermore, samples with high expression of STC1 had worse overall survival as against samples with low STC1 expression (Su et al ., 2015). E2F2, an E2F family transcription factor, has been related to various phenotypes such as cell proliferation, cell cycle, apoptosis and DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, one cluster consisting of just three proteins -chemokine (C-X-C motif) ligand 1 (CXCL1), matrix metallopeptidase 1 (MMP1), and stanniocalcin 1 (STC1) -were very highly present in the sSASP of all inducers, suggesting that these proteins are best qualified to serve as surrogate markers of the sSASP. Of note, among the top expressed sSASP proteins was STC1, a previously unidentified SASP factor and a secreted hormone with many disease associations Du et al, 2016;Ohkouchi et al, 2015;Pan et al, 2015;Shahim et al, 2017;Su et al, 2015), demonstrating the utility of robust unbiased approaches to uncovering novel molecules, biological functions and pathways. Our approach also validates MMP1 and CXCL1 as SASP markers.…”
Section: Senescence-inducing Stresses Drive Largely Distinct Secretormentioning
confidence: 99%